PRODUKSI Gracilaria verrucosa YANG DIBUDIDAYAKAN DI TAMBAK DENGAN BERAT BIBIT DAN JARAK TANAM YANG BERBEDA - Widiastuti, Irawati Mei (AgriSains, 2011)
The purpose of the research was to identify the highest production of Gracilaria verrucosa cultivated in a sea-fish pond with different seed weights and different plantation intervals.           The research hipothesis was that there was an interaction between different seed weight and planting interval on Gracilaria  verrucosa production. The research was done for 50 days. This research used a Completely Randomized Design in a Two Factorial Experiment with three replicates. The first factor was seed weights: 50 g, 100 g and 150 g. The second factors was plantation intervals included 10 cm, 20 cm, and 30 cm ntervals. The measured parameter was production of Gracilaria verrucosa. Data was analized by ANOVA and Least Significant Difference if the ANOVA result showed significant effect. The planting of Gracilaria verrucosa seaweed using different seed weights and planting intervals was significantly influenced the production of Gracilaria verrucosa. The highest seaweed growth  was was found at 50 g seed weight with 30 cm planting interval and 100 g seed with planting interval 10 cm (590,27 g m-1). The water quality in the research site still good for planting Gracilaria verrucosa seaweed. Key words: Gracilaria verrucosa, production, seaweed.